TANGGUNG JAWAB HUKUM ATAS KESALAHAN PEMBERIAN PENJELASAN TINDAKAN KEDOKTERAN OLEH TENAGA KESEHATAN - Rury Dewi (The Juris, 2026)
The provision of medical information (informed consent) is a mandatory duty of physicians that is frequently misdelegated to nurses or midwives, thereby increasing the risk of medical errors and malpractice. Objective: This study aims to analyze the legal framework governing medical explanations and identify the forms of legal liability arising from errors in this process under Indonesian regulations. Method: This study employs a normative legal research method with a statute approach and a conceptual approach. Results: The findings indicate that based on Article 293 of Law No. 17 of 2023 concerning Health juncto Minister of Health Regulation No. 290/2008, medical explanations must be delivered directly by the attending physician. Delegation to other healthcare professionals is only legally valid if it adheres to Standard Operating Procedures (SOPs) and remains under the physician's supervision. Errors or defects in fulfilling informed consent due to negligent information transfer can trigger three cumulative clusters of legal liability: administrative sanctions, civil liability based on breach of contract or torts, and criminal liability under Article 440 of the Health Law if negligence results in severe injury or death.